METAL ION INTERACTIONS WITH POLY(2-ACRYLAMIDE-2- METHYL-1-PROPANESULFONIC ACID-co-METHACRYLIC ACID) - RIVAS,BERNABE L. (Sociedad Chilena de Química, 2000)
Three copolymers of 2-acrylamide-2-methyl-1-propanesulfonic acid and methacrylic acid have been synthesized. The interactions of these copolymers and the corresponding homopolymers with Cu2+, Cd2+, Co2+, Cr3+, Zn2+, Ni2+, and Ag+ have been analyzed as a function of the pH by the use of the ultrafiltration technique. A typical polyelectrolyte behavior has been observed.